Drawing power of virtual crowds. Issue 145 (15th August 2018) - Jorjafki, Elham Mohammadi; Sagarin, Brad J.; Butail, Sachit
Abstract : In 1969, social psychologist Milgram and his colleagues conducted an experiment on a busy city street where passers-by witnessed a set of actors spontaneously looking up towards a building. The experiment showed that the crowd's propensity to mimic the actor's gaze increased with the number of actors that looked up. This form of behavioural contagion is found in many social organisms and is central to how information travels through large groups. With the advancement of virtual reality and its continued application towards understanding human response to crowd behaviour, it remains to be verified if behavioural contagion occurs in walkable virtual environments, and how it compares with results from real-world experiments. In this study, we adapt Milgram's experiment for virtual environments and use it to reproduce behavioural contagion. Specifically, we construct a replica of an indoor location and combine two established pedestrian motion models to create an interactive crowd of 60 virtual characters that walk through the indoor location. The stimulus group comprised a subset of the characters who look up at a random time as the participants explore the virtual environment. Our results show that the probability of looking up by a participant is dependent on the size of the stimulus group saturating to near certainty when three or more characters look up. The role of stimulus size was also evident when participant actions were compared with survey responses which showed that more participants selected to not look up even though they saw characters redirect their gaze upwards when the size of the stimulus group was small. Participants also spent more time looking up and exhibited frequent head turns with a larger stimulus group. Results from this study provide evidence that behavioural contagion can be triggered in the virtual environment, and can be used to build and test complex hypotheses for understanding human behaviour in a variety of crowd scenarios.